2016
DOI: 10.1016/j.jid.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Human β-Defensin 3 and Its Mouse Ortholog Murine β-Defensin 14 Activate Langerhans Cells and Exacerbate Psoriasis-Like Skin Inflammation in Mice

Abstract: Our data show that one-third of patients with PD have autoantibodies to Col XVII that also bind to TH þ neurons. The lack of reactivity of PD autoantibodies with skin suggests the autoantibodies develop from neuronal Col XVII. The subset of patients with neurologic disease that develop BP likely result from epitope spreading to regions of Col XVII that are pathogenic in skin. A key question that remains is whether Col XVII autoantibodies have a detrimental effect on PD or are otherwise predictive of disease on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Although DCs and T cells are known to play important roles in the pathogenesis of psoriasis, the role of LCs in mouse models of psoriasis-like inflammation is controversial [22][23][24][25][26][27]. LCs were reported to function of a negative immunoregulatory role via IL-10 and programmed cell death ligand-1 during the initiation and progression of psoriasis [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DCs and T cells are known to play important roles in the pathogenesis of psoriasis, the role of LCs in mouse models of psoriasis-like inflammation is controversial [22][23][24][25][26][27]. LCs were reported to function of a negative immunoregulatory role via IL-10 and programmed cell death ligand-1 during the initiation and progression of psoriasis [22].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, LCs were required for the development of IMQ-treated psoriasis like inflammation in langerin-DTR KI mice [24,25]. In addition, human β-defensin 3 (HBD3) sustained and amplified psoriasis inflammation and HBD3 drived the production of IL-23 by LCs in psoriasis, which contributed to the pathogenesis of psoriasis [26]. Therefore, to elucidate the role of LCs in the pathogenesis of psoriasis, we used K5.Stat3C:langerin DTR KI mice, in which LCs could be depleted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, an in vitro study of the human skin found that human LCs efficiently induced IL-22-producing CD4 + T cells [41], which may support the finding in our study that LCs are involved in the induction of IL-22 from T cells. Furthermore, it has been recently reported that activation of LCs by human b-defensin 3 sustained and amplified an IMQ-induced inflammation in mice [42]. However, currently it is not clear how murine LCs specifically regulate gd low T cells to produce IL-17A and IL-22 upon IMQ application.…”
Section: Discussionmentioning
confidence: 99%
“…In the dermis, inflammatory DCs accumulate and contribute to the inflammatory environment through the production of tumor necrosis factor (TNF), inducible nitric oxide synthase, IL-12 (Brunner et al, 2013;Guttman-Yassky et al, 2007;Hansel et al, 2011;Lowes et al, 2005;Zaba et al, 2009), and IL-23 (Cai et al, 2011;Lee et al, 2004;Teunissen et al, 2012;Tonel et al, 2010;Yawalkar et al, 2009). In lesional epidermis, LCs display impaired migrational capacity (Cumberbatch et al, 2006;Shaw et al, 2010); elevated expression of CXCL9, CXCL10, and CCL20 (Fujita et al, 2011); and increased IL-23 production in response to TLR3 stimulation (Sweeney et al, 2016). Compared with LCs, epidermal DCs (eDCs) in lesional psoriasis display similar or higher gene expression of chemokines (Fujita et al, 2011).…”
Section: Introductionmentioning
confidence: 99%